Penegakan Hukum Bagi Pelaku Tindak Pidana Kekerasan Seksual Terhadap Anak (Studi Kasus Putusan Nomor 482/Pid.Sus/2021/PN) - Patty, Reynalda Fransin; Wadjo, Hadibah Zachra; Patty, Jetty Martje (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: sexual deviation where this leads to an unbalanced activity that poses a threat to certain individuals. Various kinds of sexual choices are being discussed in cases of violence, especially against children. Causing a deterrent effect is felt to be less able to have such a significant impact because the perpetrator of the psychological deviation is not only one child. The decision given by the court is very necessary to provide a deterrent effect to perpetrators of sexual violence against children, so that the incidence of sexual violence in Indonesia is decreasing.Purposes of the Research: The purpose of this study is to provide an overview of law enforcement in Indonesia against perpetrators of sexual violence against children, and to provide an overview of the role of law enforcement officers in taking action against perpetrators of sexual violence against children. Methods of the Research: The research method used in this paper consists of various methods and activities carried out in order to collect the data and materials needed to complete the preparation of the. The author uses a normative juridical research method.Result of the Research: The results of this study are that the District Court's decision only considers the elements that are fulfilled and the ability to equip criminal acts that elevate while in the High Court's decision it considers the consequences obtained by the victim's child and the victim's family where the victim's child and family enjoy shame, costs to care for, enlarge and educate the child to be born by the victim's child, besides the decision given by the high court 2 (two) years higher than the decision of the District Court aims to provide a deterrent effect and awareness of the actions committed by those who have destroyed the future victim's child.